Swamp spies - DeLeon, Jana (DeLeon, Jana. Miss Fortune mystery, 2024)
"Things have reached a critical point in the Middle East. Carter agreed to serve as a consultant for his old Force Recon unit but for reasons unknown to his friends and family, jumped from the command center and into the field. Now he's MIA, and Fortune is the only one who can put together a rescue mission that has any chance of being successful. But will her skills and connections be enough? Most Sinful residents are unaware of Carter's crisis and are going about their daily lives as they always have, including local prankster Gage Babin. Except this time, Gage's attempt to elicit laughs leaves him on a slab in the medical examiner's office. Everyone knows how unhealthy he was, but Fortune thinks there's more to his death than a poorly timed prank that caused his bad heart to give out. Unfortunately, what she knows and what she can prove are two different things. And unless she can find the evidence to support her theory, someone will get away with murder" -- Amazon.com.